TRADISI MALAM SELIKURAN KRATON KASUNANAN SURAKARTA - Syamsul Bakri; Siti Nurlaili Muhadiyatiningsih (IBDA` : Jurnal Kajian Islam dan Budaya, 2019)
Abstract: This paper describes the process of constructing a tradition called as Malem Selikuran in Keraton Kasunanan Surakarta, the meaning of symbol in Malem Selikuran, and the relevance of the symbolic meaningtoward the people’s lives. The analytical methods implemented in this paper were historical continuity, verstehen and hermeneutic. The results are synthesized as the following. First, Malem Selikuran tradition is ahistorical product of the process from adaptation of Islam in Javanese culture. This religious cultural product simultaneously became a distinctive religious characteristic in Keraton Kasunanan Surakarta, as the successorto the relay of the Islamic Javanese Kingdom of Mataram. Second, the tradition has the orders of moralities that apply symbolic language. Javanese people use the symbols to convey moral and religious messages. The message of Malem Selikuran ritual with various ritual equipment shows that the people of Surakarta Kasunan Palace uphold the importance of maintaining the harmony between humans and Allah SWT, and also between humans and the universe (amemayu hayuning bawana) based on the spirit of monotheism, morals and sufism. Third, the relevance of the symbolic meaning of Selikuran Keraton Surakarta for the people’s lives is on the historical and cultural plains. Historically, the ceremony of it reminds us of how Islam and Javanese culture havedistinctive characteristics of integration in the history of Islamization in Java. Likewise, culturally, Malem Selikuran tradition is a creative work of Muslims in Java in order to give an identity to their community.